Análise da sustentabilidade ambiental do uso e ocupação do solo no município de Ilha Comprida-SP - Jesus, Adriana Rita Guarnieri de (Universidade Federal de São Carlos, 2002)
The present work consisted in the application of a method for environmental sustainability analysis for land use and soil occupation of Ilha Comprida city, located in the southern state of São Paulo, the estuarine-lagoon complex Iguape-Cananéia- Paranaguá, region of Vale do Ribeira de Iguape. Land use and soil occupation of Ilha Comprida and the concept of sustainability as a theoretical, technical and empirical supporting body were studied. This work used a methodology based on a Method developed by a Study Group from UFSCar (Federal University of São Carlos) called Strategic Planning and Sustainable Urban Environment (PESMU), which incorporates the sustainability issue in the analysis and evaluation of urban context projects. Therefore, the methodology makes use of flow charts, interaction matrices, characterization sheets, used together, directing the analysis of environmental sustainability in the city, pointing favorable, neutral or unfavorable trends to environmental sustainability. Practical applications of the method in different areas of the city were carried out, showing the land use and soil occupation as the action variable (street construction layout, plot, deployment of building plots, urban uses and buildings geometries) and environmental issues as control variables. Comprising an easy applicability methodology, it proved to be feasible, and can be added other possible information and more complex analysis tools to enable the expansion of its applicability.
Keywords: Engenharia urbana; Sustentabilidade ambiental; Política ambiental; Saneamento urbano; Uso e ocupação do solo urbano; Capacidade de suporte; Sustainability; Urban sanitation; Land use and urban land use; Carrying capacity; ENGENHARIAS